Recurrent oral submucous fibrosis with nil mouth opening surgical management and reconstruction with bilateral nasolabial flap: A case report and review of literature - Kamal Kanthan Ravikumar; U Nausath Khan; Priyadarshini; Karthik Ramakrishnan; S Nachiappan (Wolters Kluwer Medknow Publications, 2019)
Oral submucous fibrosis [OSF] is a premalignant condition characterized by inflammation and progressive fibrosis of submucosal tissue, resulting in trismus. It is associated with chewing of areca nut in betel quid. Mortality rate is significant because it transforms into oral squamous cell carcinoma at a rate of 2.3%-7.6%. The aim of this article is to share our experience in managing a case of recurrent oral submucous fibrosis with nil mouth opening by surgical excision, coronoidotomy, and reconstruction of buccal defect using bilateral inferiorly based nasolabial flap, followed by active oral physiotherapy. The patient had reached an acceptable mouth opening with no further recurrence. The patient was observed closely for any malignant transformation. Surgical excision of bands and coronoidotomy followed by reconstruction with nasolabial flaps and active physiotherapy in the postoperative period remains a good option for recurrent and advanced cases of OSF with acceptable functional and cosmetic results.